การประยุกต์ใช้คอมพิวเตอร์ในการวิเคราะห์คุณสมบัติของดินบดอัดสำหรับงานถนน - อารีย์พงศ์, ธนานันต์; จันทรุไทย, ปิติ; จริตงาม, สราวุธ (Wichcha Journal Nakhon Si Thammarat Rajabhat University, 2014)
บทความนี้ศึกษาคุณสมบัติของดินบดอัดสำหรับงานถนน เพื่อทดสอบและแนะนำวัสดุสำหรับงานฐานราก ดินฐานรากมีความสำคัญในการแบกรับน้ำหนักดินถมคันทางและชั้นโครงสร้างทางตลอดจนน้ำหนักยานพาหนะที่กดทับตลอดเวลา จึงต้องมั่นใจว่าดินฐานรากมีความสามารถในการรับน้ำหนักได้และไม่เกิดการทรุดตัวทั้งในขณะก่อสร้างและใช้งาน ในการศึกษาได้ทำการทดสอบค่ารับน้ำหนักของดินโดยวิธี Plate Load Test เพื่อตรวจสอบการทรุดตัว(Settlement) ของดินฐานราก และหาค่า California Bearing Ratio (CBR) ของดินฐานรากตำแหน่งเดียวกัน ผลการทดสอบพบว่าค่า CBR ทั้งแบบ Soaked และ Unsoaked และการทรุดตัว (Settlement) ของดินฐานรากทุกจุดมีค่าอยู่ในเกณฑ์ที่กำหนด และสามารถใช้เป็นวัสดุฐานรากได้ A Computer Application for the Properties Analysis of Soil Compaction for Road Work This paper is to study the properties of an attribute soil compacted for the road construction. For testing and suggest a material to use in work of Mechanically Stabilized Earth Wall (MSE wall) foundation that this foundation soil is important to bear Subgrade’s weight and Layer structure including Vehicle’s weight that always press, to make sure that this kind of foundation soil has capability to bear a weight and not settlement. This case study has testing Ultimate Soil – Bearing Capacity with Plate Load Test method for base soil settlement checking and find California Bearing Ratio (CBR) value of foundation soil. Results of the study showed that CBR value in Soaked and Unsoaked and settlement of foundation soil in every position is in standard value and can use for foundation material.